Structural basis of adaptor-mediated protein degradation by the tail-specific PDZ-protease Prc - Ming-Yuan Su (Nature Portfolio, 2017)
MepS is a peptidoglycan (PG) cross-link specific hydrolase needed for cell wall expansion and its cellular levels must be tightly regulated. Here the authors present the structure of the MepS degrading protease Prc bound to its adaptor NlpI and propose a model how the NlpI-Prc complex mediates MepS degradation.